1999
DOI: 10.1029/1999jc900213
|View full text |Cite
|
Sign up to set email alerts
|

A case study of air‐sea interaction during swell conditions

Abstract: , appearing abruptly at wave age co/Uw equal to 1.2. Turbulence spectra of the horizontal components were shown not to scale with height above the water surface, in contrast to vertical velocity spectra for which such a variation was observed in the low-frequency range. In addition, spectral peaks in the horizontal wind spectra were found at a frequency as low as 10 -3 Hz. From a comparison with results from a previous study it was concluded that this turbulence is of the "inactive" kind, being brought down fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
117
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 26 publications
13
117
0
Order By: Relevance
“…Smedman et al (1999) found that, although the phase speed of the relatively long waves was indeed influenced by shallow water effects, little effect on the turbulence structure in the atmospheric surface layer was observed. In Smedman et al (2003) a comparison was made of roughness length z 0 (m) for pure wind sea conditions (young waves) fromÖstergarnsholm and from deep sea expeditions.…”
Section: The Measurement Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Smedman et al (1999) found that, although the phase speed of the relatively long waves was indeed influenced by shallow water effects, little effect on the turbulence structure in the atmospheric surface layer was observed. In Smedman et al (2003) a comparison was made of roughness length z 0 (m) for pure wind sea conditions (young waves) fromÖstergarnsholm and from deep sea expeditions.…”
Section: The Measurement Sitementioning
confidence: 99%
“…At about 10 km from the peninsula the water depth is 50 m, reaching below 100 m farther out. In Smedman et al (1999) the possible influence of limited water depth on the tower measurements was studied in detail. Flux footprint calculations were done, showing that the turbulence instruments 'see' areas far upstream of the island.…”
Section: The Measurement Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Swell loses energy to the atmosphere as it gradually decays [2,23], accelerating the airflow at lower altitudes, in the form of the so called "wave-driven wind", inducing a departure from the logarithmic wind profile [15,21]. For this reason swell has a consistent influence on the overall turbulence structure of the boundary layer, since it reduces the wind shear in the MABL and consequently the mechanical production of turbulence [14,15,18,22,23]. Under the wave-growing process, energy is transferred to the ocean throughout vertical transport of horizontal momentum via momentum flux, which drives currents, generates waves, and triggers wave breaking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as swell waves propagate into light wind areas they perform work on the overlying atmosphere, inducing a pressure perturbation in the first few meters of the marine atmospheric boundary layer (MABL), producing a forward thrust on the flow [14,17,21,22]]. Swell loses energy to the atmosphere as it gradually decays [2,23], accelerating the airflow at lower altitudes, in the form of the so called "wave-driven wind", inducing a departure from the logarithmic wind profile [15,21]. For this reason swell has a consistent influence on the overall turbulence structure of the boundary layer, since it reduces the wind shear in the MABL and consequently the mechanical production of turbulence [14,15,18,22,23].…”
Section: Introductionmentioning
confidence: 99%